Ecossistemas criativos: relações colaborativas e ação projetual nos coletivos criativos informais - Velasques, Taline Sabany (Universidade do Vale do Rio dos Sinos, 2016)
The collaborative practices, contemporary times characteristic, are increasingly present in the workplace. This happen due the fact it's interactive character in the fusion of values and results between different actors involved in a network of cooperation for joint problem solving. Thus, the research that follows aims to reflect on the creative clusters, collaborative environments in order to create opportunities creativity, collaboration, exchange of experience, proposing a specific study on the informal spaces of collaboration. The study aims to analyze the strategic role of the designer in informal creative clusters, trying to understand if there is the use of metadesign and if so, if the use of this methodological approach generates contributions in informal settings. The research applied a single case study, in Casa Liberdade, informal creative cluster whose context presented an open and independented model. As data collection instruments, interviews were conducted and cluster documents were gathered. The research’s main contribution it is to promote reflections on the informality advantages in the collaborative context, proposing new ways of thinking design and the designer in collaborative and informal atmosphere.
Keywords: Ecossistemas criativos; Coletivos criativos; Informalidade; Metaprojeto; Relações colaborativas; Creative ecosystems; Creative collectives; Informality; Metadesign; Collaborative relationships; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial